Algorithmic Art and the Transformation of Public Spaces: Hybrid Public Spaces. - OKTAN, Kevser AKYOL; ULUSOY, M. Demet (Journal of Faculty of Letters / Edebiyat Fakultesi Dergisi)
Algorithmic art, one of the new art forms that emerged in line with the effects of digitalization in the field of art, is not only limited to digital installations integrated into physical spaces or three-dimensional installations in which physical space is transformed through digital images but also offers a hybrid spatial experience through artistic expressions that expand via social networks. When this aspect of algorithmic art is considered together with discourses on the democratization of art, it stands out as an important issue that opens up discussions about the possibilities offered by art in the context of hybrid public space. An inquiry carried out in this direction can offer new expansions within the framework of the "art for everyone" approach. In this study, the dynamics between algorithmic art and hybrid public space are examined using a qualitative research design and a case study method, and a model proposal is presented by evaluating the potential of hybrid public spaces and algorithmic art. In this context, the proposed model is structured within the framework of five basic categories - accessibility, inclusiveness, relationality, personalization of experience and collective sensation - and the art projects of Refik Anadol, one of the leading names in algorithmic art, are analyzed within the scope of this model. Based on the findings, the study demonstrates that constructing hybrid public spaces--particularly in the context of Refik Anadol's projects--significantly enhances the accessibility of artistic experience, fosters a pluralistic approach in artistic expression, dismantles the hierarchy between the work of art and the audience, individualizes the artistic experience, reveals individuals' relationships with other forms of existence, and cultivates a collective sensation in accordance with this relational structure.